2015
DOI: 10.1088/0268-1242/30/10/105034
|View full text |Cite
|
Sign up to set email alerts
|

Low resistive Au-free, Ta-based, recessed ohmic contacts to InAlN/AlN/GaN heterostructures

Abstract: The formation of recess etched Au-free ohmic contacts to an InAlN/AlN/GaN heterostructure is investigated. A Ta/Al/Ta metal stack is used to produce contacts with contact resistance (R c ) as low as 0.14 Ω mm. It is found that R c decreases with increasing recess depth until the InAlN barrier is completely removed. For even deeper recesses R c remains low but requires annealing at higher temperatures for contact formation. The lowest R c is found for contacts where the recess etch has stopped just above the 2D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…The recess etch was made with a low power Cl/Ar-plasma, and the metal stack was Ta/Al/Ta (10/280/20 nm). [12][13][14] After annealing at 550 C, the contact resistance was measured to be 0.33 X Â mm. The gates were defined in a two-step electron-beam lithography process.…”
Section: à3mentioning
confidence: 99%
“…The recess etch was made with a low power Cl/Ar-plasma, and the metal stack was Ta/Al/Ta (10/280/20 nm). [12][13][14] After annealing at 550 C, the contact resistance was measured to be 0.33 X Â mm. The gates were defined in a two-step electron-beam lithography process.…”
Section: à3mentioning
confidence: 99%
“…Recessed and Ta-based ohmic contacts produced contact resistances of %0.3 Ω mm as extracted from transmission line measurements for all samples. [21][22][23] HEMTs with gate lengths (L g ) of 40, 70, 100, 150, and 200 nm, a gatesource distance (L GS ) of 1 μm, gate-drain distances (L GD ) of 1 and 2.5 μm, and a gate width of 2 Â 50 um were fabricated. The dimensions were verified with a scanning electron microscope.…”
Section: Methodsmentioning
confidence: 99%
“…%) typically require a high alloy temperature while, in agreement with our observations, the optimum alloy temperature is typically in the 500-600°C range for Al-rich ohmic metal stacks. 16) For both Au-containing [20][21][22][23][24] and Au-free ohmic contacts, [25][26][27][28][29][30][31] it was shown that the ohmic contact resistance can be further improved by partial or complete removal of the AlGaN barrier. Indeed, because of the insulating nature of the AlGaN barrier, ohmic contact formation relies partly on carrier tunneling across this barrier, and partial or complete removal of the AlGaN barrier was shown to facilitate ohmic contact formation.…”
Section: Introductionmentioning
confidence: 99%